2020
DOI: 10.1007/s10803-020-04368-9
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functioning in 60+ Autistic Males: The Discrepancy Between Experienced Challenges and Cognitive Performance

Abstract: As executive functioning (EF) is especially sensitive to age-related cognitive decline, EF was evaluated by using a multimethod assessment. Fifty males (60-85 years) with a late adulthood autism spectrum condition (ASC) diagnosis and 51 non-ASC males (60-83 years) were compared on cognitive tests across EF domains (cognitive flexibility, planning, processing speed, and working memory) and a self-and proxy report of the Behavior Rating Inventory of Executive Function-Adult Version. While no objective performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 38 publications
5
40
0
2
Order By: Relevance
“…Furthermore, we used Bayesian replication analyses (Ly, Etz, Marsman, & Wagenmakers, 2019;Verhagen & Wagenmakers, 2014), which uses the data from the original study as a prior for the current results -maximizing the use of prior knowledge. Based on the previous study by Lever and colleagues (Lever & Geurts, 2016;Lever et al, 2015), and studies with older adult samples (Davids, Groen, Berg, Tucha, & van Balkom, 2016;Geurts, Pol, Lobbestael, & Simons, 2020;Geurts & Vissers, 2012;Tse et al, 2019) we expected: (1) worse performance of ASC than comparisons on ToM, fluency, and processing speed, better performance of ASC than comparisons on visual memory, and equal performance on visual working memory (2) either a similar relation with age (verbal memory, fluency and processing speed) or a smaller negative relation with age (visual memory, working memory and ToM) for ASC than comparisons.…”
Section: Lay Summarymentioning
confidence: 99%
“…Furthermore, we used Bayesian replication analyses (Ly, Etz, Marsman, & Wagenmakers, 2019;Verhagen & Wagenmakers, 2014), which uses the data from the original study as a prior for the current results -maximizing the use of prior knowledge. Based on the previous study by Lever and colleagues (Lever & Geurts, 2016;Lever et al, 2015), and studies with older adult samples (Davids, Groen, Berg, Tucha, & van Balkom, 2016;Geurts, Pol, Lobbestael, & Simons, 2020;Geurts & Vissers, 2012;Tse et al, 2019) we expected: (1) worse performance of ASC than comparisons on ToM, fluency, and processing speed, better performance of ASC than comparisons on visual memory, and equal performance on visual working memory (2) either a similar relation with age (verbal memory, fluency and processing speed) or a smaller negative relation with age (visual memory, working memory and ToM) for ASC than comparisons.…”
Section: Lay Summarymentioning
confidence: 99%
“…18,19 While the standard U.S. Census demographic criteria for older adulthood use a threshold of 65 years of age, important variability, heterogeneity, and age-related change exist within this age group. [20][21][22][23] Autism is associated with important age-related variables such as physical health, [24][25][26][27] cognitive performance, 28,29 and psychological well-being. [30][31][32][33][34][35] In addition to their implications for overall quality of life, these challenges have ancillary impacts on families and caregivers, a significant financial impact, and the potential to create greater risk of acute and chronic disease burden across the life span.…”
Section: Introductionmentioning
confidence: 99%
“…In studies including autistic children, typically medium effect sizes are observed and performance differences are apparent across a broader range of cognitive domains [16]. Moreover, independent empirical studies including old autistic individuals recently reported similar findings as Lever and colleagues observed [17,18]. So, in sharp contrast to the dominant hypothesis, these novel findings suggest that with increasing age, the cognitive differences between autistic adults and non-autistic adults become less pronounced.…”
Section: Introductionmentioning
confidence: 68%